Circuits of Compassion: The Affective Labor of Uganda's Christian Orphan Choirs. (13th September 2020) - Boyd, Lydia
Abstract: Uganda's touring orphan choirs engage in a form of charity that is dependent on the mobility not only of money, but also of people and sentiments. Boyd considers the moral economies that underlie this ongoing project of compassionate "circulation." If a key finding of the work on humanitarian affect has been how such "affective surpluses" mask inequalities between donors and recipients, this article considers how participants in charitable relationships conceive of dependency and indebtedness differently. These differences compel us to understand how moral and religious sentiments give shape to the inequalities inherent in dominant forms of global humanitarian "care."